The ethics of dissent managing guerrilla government - O'Leary, Rosemary 1955- (CQ Press, 2020)
From “constructive contributors”" to “deviant destroyers,” government guerrillas work clandestinely against the best wishes of their superiors. These public servants are dissatisfied with the actions of the organizations for which they work, but often choose not to go public with their concerns. In her Third Edition of The Ethics of Dissent, Rosemary O’Leary shows that the majority of guerrilla government cases are the manifestation of inevitable tensions between bureaucracy and democracy, which yield immense ethical and organizational challenges that all public managers must learn to navigate.